THE EFFECTIVENESS OF ANIMATION FILM TO IMPROVE STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT ATFIRSTGRADE SENIOR HIGH SCHOOL 12 PEKANBARU - Jacenda, Zennet; ', Eliwarti; ', Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study is to find out the effectiveness of the first grade students’ ability of SMAN 12 Pekanbaru in writing narrative texts.The participants were 75 students. The data were collected using writing test. The research finding indicated that the application of using animation filmas a media could improve students’ writing ability. The result of pre-test showedthat the mean score of the students in experiment class was 47,68 and in control class was 45,08. The result of post-test showed that the mean score of the students in experiment class was 62,86 and in control class was 54,86.From the t obs result, it can be seen that the experiment class get score (23) and the control class (10,74). After obtaining the standard deviation both of experimental and control group, the standard error can be calculated. The standard error was 1,121 and the t table was 7,13.The data analysis technique was show whether the mean different was significant (t obs> t table). From the research finding, it can be concluded that using animation film can motivate students to engage in language learning.Thus, based on the above explanation, the writer concludes that using animation film is effective in improving students ability in writing narrative text.Keywords: Animation Film, Writing, Narrative Texts.